2022
DOI: 10.1017/s0007114522000241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary and exercise treatments on HDL subclasses in lactating women with overweight and obesity: a secondary analysis of a randomised controlled trial

Abstract: Childbearing decreases High Density Lipoprotein cholesterol (HDL-C), potentially contributing to the increased risk of cardiovascular disease (CVD) in parous women. Large HDL particles (HDL-P) are associated with lower risk of CVD. In this secondary analysis of a randomised controlled trial, we investigated the effects of 12-week Dietary and Exercise treatments on HDL-P subclass concentration, size and apolipoprotein A1 (apoA1) in lactating women with overweight/obesity. At 10-14 weeks postpartum, 68 women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Increased particle number, cholesterol and phospholipid concentrations of large HDL particles were correlated with opposite changes in large VLDL particles, possibly due to the reduced dietary intake and/or increased exercise accelerating VLDL particle lipolysis and concomitant lipid transfer to HDL particles. 21,22 A similar link between the metabolism of triglyceride-rich particles and HDL was also proposed in an NMR-spectroscopy study in lactating women, 23 where both diet-and exercise-induced weight loss conditions were found to have favorable effects on the size and phospholipid concentration of HDL particles. Furthermore, our previous study found decreased level of lipoprotein lipase inhibitors in the end of the competitors' fat loss period, 13 suggesting that enhanced VLDL lipolysis could have contributed to the increased HDL lipid concentrations.…”
Section: Discussionmentioning
confidence: 60%
“…Increased particle number, cholesterol and phospholipid concentrations of large HDL particles were correlated with opposite changes in large VLDL particles, possibly due to the reduced dietary intake and/or increased exercise accelerating VLDL particle lipolysis and concomitant lipid transfer to HDL particles. 21,22 A similar link between the metabolism of triglyceride-rich particles and HDL was also proposed in an NMR-spectroscopy study in lactating women, 23 where both diet-and exercise-induced weight loss conditions were found to have favorable effects on the size and phospholipid concentration of HDL particles. Furthermore, our previous study found decreased level of lipoprotein lipase inhibitors in the end of the competitors' fat loss period, 13 suggesting that enhanced VLDL lipolysis could have contributed to the increased HDL lipid concentrations.…”
Section: Discussionmentioning
confidence: 60%